Contemporary Human Resource Management : Text and Cases - Wilkinson, Adrian; Dundon, Tony (SAGE Publications, Ltd. (UK), 2021)
Written by experts in the field, this well-established book provides a critical and academically rigorous exploration of the key functions, practices and issues in HRM today. The first part of Contemporary Human Resource Management covers fundamental HRM practices while the second half examines contemporary themes and issues such as work-place bullying, flexibility and emotion at work. Each chapter contains two thought-provoking case studies, encouraging readers to identify, examine and apply key concepts to real-world examples. This substantially revised sixth edition includes three completely new chapters and case studies on: HRM in SMEs The Future of Work Employee Wellbeing